Awareness and Availment of Pension Benefits of Military Pensioners in Bacolod City - Montaño, Febe Anne F.; Tinagan, Romeo R. (Philippine Social Science Journal, 2020)
Pension is a necessity and a vital investment to ensure financial security after retirement. Primary pensioners need to transition to civilian life and the surviving spouses of deceased veterans facing widowhood. Maximizing the availment of pension benefits will alleviate the financial distress of military pensioners and promote life satisfaction after many years in the military service. The study was conducted to determine the awareness and availment of the pension benefits of military pensioners and the challenges they have encountered in availing of these benefits. The findings of this study were utilized to prepare an action plan to cater better to the concerns of primary pensioners and surviving spouse beneficiaries.